ASSESSING THE ROLE OF ICT IN THE MANAGEMENT OF COVID-19 SAFETY MEASURES DURING THE 2020 LOCKDOWNIN KANO STATE (Wudil Journal of Science and Technology Education, 2025)
ICT stands for Information and Communication Technology. It is a generic term referring to atechnology being used for collecting, storing, editing, and processingof information in variousforms. Similarly, COVID-19 is a disease that has posed a devastating impact on public health inthe world and Nigeria in particular. Above all, it has crippled theeconomic and socialactivitiesof the people as a result of the persistent lockdown imposed at various regular intervals when thedisease was at its height in 2020. Against this background, therefore, this paper is a reflection onthe role of ICT as it can be applied for the management of COVID-19 safety measures and otherdisease outbreaks in the country in the future. The paper examine the concept of informationtechnology in the management of COVID-19 in Kano State. It also reviews some research workrelated to the role of management of information technology in keeping the people fully informedabout their responsibilities in curtailing the spread of the virus. Methodologically, the paperuses a descriptive survey method and purposive sampling technique, which allows the selectionof five local governments in Kano state, namely: Fagge, Dala, Nasarrawa, Tarauni, and Gwalelocal governments area of Kano State. Five fundamental questions were raised, in which 20respondents were randomly selected from each of the local governments, and the questionswereadministered to them. Data presentation and analysis: the result of the data from the field wasanalysed using percentages (%). The findings of the study reveal that ICT can be used to manageCOVID-19 and any other disease outbreak in the future in Kano state. It also states that thepower supply can limit the effective use of ICT in the state. The paper provides somerecommendations for improvement in power supply and an increase in government funding ineconomic activities and the production of ICT materials.
Keywords: Information and Communication Technology, Covid-19, SafetyMeasures and Management.